Terrorism in Cyberspace: A Case Study of Terrorist Organizations Operating in Pakistan - Iqbal, Zaheema (Cyberpolitik Journal, 2020)
The presence of extremist and radical groups on internet is an old phenomenon as they have been manifesting their appearance in cyber space since their very own inception. However, their dependency in cyberspace operations has enormously expanded since last two decades. The cyber terrorism threat has evolved into a multi-faceted and complex riddle where various ideological dogmas are turning the world into a cyber-war. By 2000, all terrorist groups virtually had set up their online presence. This study aims to map cyber space activities conducted by terrorist organizations operating in Pakistan. How terrorist organizations are making their presence online and how do these outfits use social media for assistance and execution of terrorist attacks. The study tries to delineate case study of four terrorist organizations; Islamic State (IS), Jamat Ud Dawa (JuD), Lashker-e-Tayyaba (LeT), and Balochistan Liberation Army (BLA). The study will explore how do these organizations use cyber space for fundraising, online recruitment, psychological warfare, propaganda, and information-sharing. It will discuss existing laws in Pakistan related to cyber terrorism, challenges and a way forward.